Переписка Н. В. Гоголя: в 2 т. (Н. В. Гоголь) - Гоголь Николай Васильевич (1988)
Экземпляры: (20210301) / Инвентарный номер: 18164 / Цена: / Сис.шифр: 83.3(2Рос=Рус)1 / Авт.знак: Г 58 / ББК: 83.3(2Рос=Рус)1